Usulan Perbaikan Lean Manufacturing untuk Mengevaluasi Waste Produksi Packaging pada PT. Temprina Media Grafika - William Nico Widodo; Jani Rahardjo (Jurnal Titra, 2023)
PT. Temprina Media Grafika is a company engaged in manufacturing packaging production. In the production process PT. Temprina still needs to maximize efficiency and minimize waste. The Lean Manufacturing design uses the Value Stream Mapping method to map the existing problem conditions in the production process and evaluate them. VSM development begins with the creation of the current state VSM, then VSM Kaizen Lightening Burst to focus on the parts of the production station that will be repaired, and VSM Future State to map the flow of the production process after applying alternatives and improvements. The results of the initial analysis of the production process have a VA time of 1,738 minutes, NVA of 1.078 minutes, and a total Lead Time of 2.816 minutes. After identification, analysis, and mapping of the VSM Future State, the VA time did not change, namely 1,738 minutes, the overall NVA decreased to 387 minutes, causing the Total Lead Time to decrease to 2.125 minutes, so that the Total Lead Time experienced a faster improvement by 691 minutes or 24.54%.